ASPEK PIDANA PERDAGANGAN VALUTA ASING SISTEM DARING - Masrur Ridwan; Muhammad Shidqon Prabowo (Qistie Jurnal Ilmu Hukum, 2020)
Broker Notes mentioned that 9.6 million people in the world was doing foreign exchange trading online. It means every 1 (one) of the 781 inhabitants of the world is an online trader (in-network). Among 9.6 million traders in the world, 768,000 of them are Indonesian-language online traders. It counts almost 8%. In addition, Indonesian language traders rank fourth after English with a total of 54 percent of users, Arabic 15 percent and Spanish 10 percent of users. The next rank below Indonesia are Indian 7% consumer traders and French 6 %. The data does not clearly state that all Indonesian online valet traders use Indonesian. There can be thousands of traders online from Indonesia who choose to use English for their trading online. It means that the actual number of Indonesian residents who are online valerine traders is much greater than the number of traders who choose to use Indonesian. This paper aim to describe and illustrate how the development of information technology has quickly triggered the interest of the world population to plunge into the foreign exchange trading sector. The number of people trying to make a living for trading has steadily increased, including Indonesian people. Unfortunately, traders' interests are not offset by their knowledge and understanding of online valet trading. Traders also often have to deal with dishonest and cheating brokers. As a result, traders have to deal with not only the real issues of the trade but also the external problems from brokers. The results of this study indicate that the application of the Futures Trade Law (UN Law) No. 32 of 2008 which was later amended into Law No. 10 of 2011 with its derivative rules and Electronic Information & Transactions Act No. 11 of 2008 later amended by Law No. 19 In 2016, it was sufficient to become the legal of online system trading in Indonesia. Unfortunately, traders still find it difficult to apply for evidence when dealing with criminal cases. Meanwhile, the number of supervisors authorized to supervise is very limited, and traders themselves often do not realize that they have been "cheated".